First Epidemic of Echovirus 16 Meningitis in Cuba - Luis Sarmiento; Pedro Mas; Angel Goyenechea; Rosa Palomera; Luis Morier; Virginia Capó; Ibrahim Quintana; Manuel Santin (Emerging Infectious Diseases, 2001)
From April to September 2000, an epidemic of aseptic meningitis spread throughout Cuba, with 16,943 reported cases. Virologic studies identified echovirus 16 as the cause of this epidemic. This is the first reported isolate of echovirus 16 from patients with viral meningitis in Cuba.